Effects of Giving Flying Fish Biscuits and Jewawut Flour Against the Nutritional Status of Adolescents (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
Anthropometry is a method commonly used in assessing nutritional status, nutritional status indicators used for the adolescent age group are based on anthropometric measurements (BB) and (TB) which are presented in the form (TB/U) and (BMI/U). This study aims to determine the effect of giving biscuits with substitutes of flying fish meal and barley flour on the nutritional status of adolescent girls at SMAN 1, SMAN 2, SMAN 3 and MAN Mamuju. This research method is carried out with a Quasi Experimental study design. The population in this study were all students of class XI who were screened at SMAN 1, SMAN 2, SMAN 3 and MAN Mamuju, totaling 461 students. The results of the study on young women in high school in Mamuju district, in general, from 66 respondents from SMAN 1 Mamuju 20 people, SMAN 2 Mamuju 13 people, from SMAN 3 Mamuju 2 people and MAN Mamuju 31 people, where in the intervention and control group 100% women or teenage girl. The conclusion is that giving flying fish meal biscuits and barley flour can improve the status of weight, height, and upper arm circumference in adolescent girls.